Upregulation of TLR1, TLR2, TLR4, and IRAK-2 Expression During ML-1 Cell Differentiation to Macrophages: Role in the Potentiation of Cellular Responses to LPS and LTA. (21st May 2012) - Traore, Kassim; Zirkin, Barry; Thimmulappa, Rajesh K.; Biswal, Shyam; Trush, Michael A.
Abstract : 12-O-tetradecanoylphorbol 13-acetate (TPA) induces the differentiation of human myeloid ML-1 cells to macrophages. In the current study, the expression, responsiveness, and regulation of toll-like receptors (TLRs) in TPA-induced ML-1-derived macrophages were investigated. We have found that TPA-induced differentiation of ML-1 cells was accompanied by the upregulation of TLR1, TLR2, TLR4, and CD14 expression at both the mRNA and protein levels. Interestingly, TLR1 and TLR4 protein expression on ML-1 cells could be blocked by pretreatment with U0126, suggesting the role of an Erk1/2-induced differentiation signal in this process. In addition, the expression of IRAK-2, a key member of the TLR/IRAK-2/NF- κ B-dependent signaling cascade was also induced in response to TPA. Accordingly, we demonstrated an increased cellular release of inflammatory cytokines (TNF- α and various interleukins) upon stimulation with LPS and LTA ligands for TLR4 and TLR2, respectively. Furthermore, using luminol-dependent chemiluminescence, addition of LPS and LTA induces a sustained DPI-inhibitable generation of reactive oxygen species (ROS) by the differentiated ML-1 cells. Together, these data suggest that the increase in the responsiveness of TPA-treated ML-1 cells to LPS and LTA occurs in response to the upregulation of their respective receptors as well as an induction of the IRAK-2 gene expression.